Crisis Communication in Indonesia Football Club: Image Restoration Strategy by PSS Sleman - Mahesa Chahya Thoha Adji; Narayana Mahendra Prastya; Nadia Wasta Utami (Journal of Communication and Public Relations, 2025)
No organizations can avoid the crisis, include the football club. This paper aims to analysis the image restoration strategies by PSS Sleman, an Indonesian Football Club. On 2021, PSS experienced a crisis due to the conflict between club management and fans. PSS fans demanded resignation of clib CEO, headcoach, and one player because fans think they were causing the bad results (win-less streak). The CEO than respondend by threaten to move PSS out of Sleman. The crisis ended after all the parties stepped down and/or fired from PSS and changing in the management and coaching staff. After the crisis, organizations should do the post crisis activities to image repair. For the research method author use qualitative, with data use interview with PSS communication team (PR and media team) and fans. Data also use digital archive from PSS official media. Results PSS use two main strategies in image repair: visiting the fans directly and using social media to share official statements. The obstacles in conducting strategy : the lack of manpower in PR, no clear job description for PR, and lack of knowledge and support from the top management.